Low Overhead MAC Protocol for Low Data Rate Wireless Sensor Networks - Kien Nguyen; Yusheng Ji; Shigeki Yamada (International Journal of Distributed Sensor Networks)
We propose the low overhead media access control protocol (LO-MAC), a new low latency, energy efficient MAC protocol for low data rate wireless sensor networks. LO-MAC uses both duty cycling and multihop forwarding from the routing-enhanced MAC protocol (RMAC) to reduce idle listening and sleep latency, respectively. Besides that, LO-MAC introduces a traffic-adaptive mechanism, which is based on the fact that a node can sense a busy channel within its carrier sensing range. This mechanism uses carrier sensing as a binary signal, and effectively notifies nodes of the existence of a data packet. The nodes then either keep their radios on to take part in multihop data forwarding or turn them off to save energy. Moreover, LO-MAC takes full advantage of the broadcast nature of wireless communication and lets a packet have different meanings when it is in transmission range of different nodes. In LO-MAC, not only is a request-to-send/clear-to-send pair replaced with a Pioneer (PION) packet, as in RMAC, but also a data packet can play both data and acknowledgement functions. Therefore, control overhead and overhearing energy are significantly reduced. Our simulation results show that LO-MAC outperforms RMAC in terms of energy efficiency while achieving comparable end-to-end latency.